Communication Skills of Fresh Medical Graduates in a Malaysian Private University (Bangladesh Journal of Medical Science, 2022)
Objective: Effective communication is an integral part of good medical practice. Skills in communication is an art, and comprises of a set of fundamental elements: skills in introducing, questioning, listening, facilitating and closing. The objective of this study was to determine the perceptions of fresh medicalgraduates’ communication skills at Widad University College (WUC).Materials and Methods: It was a cross-sectional study conducted in 2019 among 50 fresh medical graduates of WUC. A standardized questionnaire that asked about skills in fundamental elements of communication with diverse people on diverse issues, was used to collect the data. The data was collated and analyzed utilising a measuring scale ranged from very well to very poor and presented using descriptive statistics.Results and Discussion: Total 46 participants responded giving a response rate 92%. The highest number of participants (79%) responded as very well in introductory skills while the lowest 59% in listening skills. In a diverse group, 70%-74% respondents communicated as very well with patients, patients’ families, superiors, support staffs and colleagues. Only 57%-67% responded as very well in breaking bad news, counselling, and taking informed-consent. Nevertheless, 2%-13% participants’ skills were very poor to uncertain, where 13% uncertain in breaking bad news and 9% in counselling and informed-consenting.Conclusion: Communication skills of most of the WUC fresh medical-graduates were very well and reasonably well. However, the art of communication does not come naturally, 2-13% of the graduates’ skills need to be consciously promoted by faculty during undergraduate training. Medical schools should give more emphasis on the development of more effective communication in all aspects of future doctors.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 404-412